INTRODUCTION TO WARUNG APPLICATION-BASED DIGITAL ACCOUNTING FOR IMPROVING THE EFFICIENCY OF FINANCIAL RECORD-KEEPING OF MSMES IN CURUG BOGOR VILLAGE - Fujianti, Lailah; Masri, Indah; Kasim, Erlynda; Aditia, Didit Pustian (LPPM Univ. Ibn Khaldun Bogor, 2025)
Efficient financial recording is a major challenge for many Micro, Small, and Medium Enterprises (MSMEs), especially in rural areas. In Curug Village, Bogor, most MSME actors still rely on manual bookkeeping which is prone to errors and difficulties in accessing financing. Therefore, this service aims to introduce digital accounting through the Warung Application, which is designed to simplify the financial recording process. The training was given to 30 MSME actors in Curug Village with the aim of improving digital financial literacy and financial recording efficiency. The methods used include providing material on the basics of accounting and the use of the application, introduction of the Warung Application in accounting recording. The results of the evaluation showed a significant increase in participants' understanding of the importance of good bookkeeping. Nonetheless, ongoing mentoring is necessary to ensure the app is used effectively in the long run. This service is expected to provide direct benefits in the financial management of MSMEs and can be expanded to other regions with similar characteristics to increase the competitiveness and sustainability of MSME businesses in Indonesia.